2022
DOI: 10.3389/fnut.2022.767415
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Dietary Diversity Score and Odds of Diabetic Nephropathy: A Case-Control Study

Abstract: A dietary diversity score (DDS) may be a useful strategy for monitoring risks associated with chronic diseases. Few studies have investigated the relationship between DDS and the progression to chronic kidney disease (CKD). A better understanding of the relationship between DDS and diabetic nephropathy (DN) may provide insight for monitoring the overall diet and clinical outcomes. This case-control study included 105 women with DN and 105 controls with age and diabetes duration-matched to evaluate the extent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…In the present study, a high DDS was found to be associated with decreased odds of MASLD. This finding is consistent with previous research that has shown an inverse association between DDS and the risk of diabetic nephropathy ( 29 ) and bladder cancer ( 30 ). In another study, by emphasizing the higher diversity scores for vegetables and fewer diversity scores for meat and refined grains, high DDS is inversely correlated with the risk of MASLD ( 15 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, a high DDS was found to be associated with decreased odds of MASLD. This finding is consistent with previous research that has shown an inverse association between DDS and the risk of diabetic nephropathy ( 29 ) and bladder cancer ( 30 ). In another study, by emphasizing the higher diversity scores for vegetables and fewer diversity scores for meat and refined grains, high DDS is inversely correlated with the risk of MASLD ( 15 ).…”
Section: Discussionsupporting
confidence: 93%
“…Numerous studies have shown that an overall dietary pattern, rather than focusing on individual foods or nutrients, is a better predictor of overall diet quality and is associated with various diseases. In particular, DDS and AHEI have been used as indicators of diet quality in relation to non-communicable diseases such as cardiovascular disease, polycystic ovaries, and some cancers ( 26 29 ). In the present study, a high DDS was found to be associated with decreased odds of MASLD.…”
Section: Discussionmentioning
confidence: 99%
“…When constructing a DDS, the food groups included were different across studies and may contribute to the inconsistent findings, partly due to the study population and purpose ( 21 , 32 , 33 , 37 ). In the literature, the classification of DDS was based on the US Department of Agriculture (USDA) food guide pyramid (five food groups), the Chinese Dietary Guideline (10 food groups), and the Food and Agriculture Organization (FAO) guidelines (9 food groups) ( 32 , 34 , 38 ). In our study, we calculated the DDS based on the dietary guidelines for Chinese populations, which additionally includes some food groups which play important roles in the Chinese diet.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that there is an inverse association between following a plant-based diet (PBD) and the risk of T2DM and its secondary outcomes. In addition, several high-quality dietary strategies, such as Dietary Approach to Stop Hypertension (DASH), Diet Diversity Score (DDS), and Mediterranean dietary pattern (MDP) containing less processed food and rich in plant-based food are associated with delayed progression of DN (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%